Schizophrenia: A Consequence of Gene-Environment Interactions? - Jonathon C Arnold (Frontiers Research Topics, 2015)
Schizophrenia is a multi-factorial disease characterized by a high heritability and environmental risk factors (e.g. stress and cannabis use). In recent years, an increasing number of researchers worldwide have started investigating the 'two-hit hypothesis' of schizophrenia predicting that genetic and environmental risk factors interactively cause the development of the disorder. This work is starting to produce valuable new animal models and reveal novel insights into the pathophysiology of schizophrenia. Eventually, it might help advance studies of the molecular pathways involved in this mental disorder and propose more specific molecular medicine. However, the complexity of this multi-factorial line of research has also caused difficulties in data interpretation and comparison. Our research topic is intended to cover past and current directions in research dedicated to the understanding and measurement of gene-environment interactions (GxE) in schizophrenia, the neurobiological and behavioural consequences of such interactions as well as the challenges and limitations one encounters when working on complex aetiological systems.